If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 56 = 4p Solving 56 = 4p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-4p' to each side of the equation. 56 + -4p = 4p + -4p Combine like terms: 4p + -4p = 0 56 + -4p = 0 Add '-56' to each side of the equation. 56 + -56 + -4p = 0 + -56 Combine like terms: 56 + -56 = 0 0 + -4p = 0 + -56 -4p = 0 + -56 Combine like terms: 0 + -56 = -56 -4p = -56 Divide each side by '-4'. p = 14 Simplifying p = 14
| (7/6)x=140 | | 16x+6y= | | 2y-3=y/3 | | 9x^2=6x-14 | | 3.09=Ln(x) | | -4.9x^2+34.3x+1=0 | | -17+2=-5(x+9) | | 3k+12+k-8-4=15+3k+2 | | .5x-4=-3-.333x | | 2x-y(2x-3)=0 | | 5/6k-1/4=1/3 | | 5/11p=-15/13 | | M-49=-38 | | -2.8x=3.15 | | 5(y+4)-8y=32 | | n-22=8 | | -0.7x+0.5+1.2x=0.5*0.8 | | R+4=14 | | 12/7z=48 | | 12x+13=97 | | (25*3*15.999)/(26.98*2) | | D/7=7 | | (25x3x15.999)/(26.98x2) | | 9+3(7d-6)+9=3d-24d | | m/12=27 | | 1/2y=3/5 | | 2x=(x-8)4 | | 5x-1.25=3x-1.25 | | -3(x+2)-42=6-33 | | (7*61)/9 | | -2(x+6)=22 | | -30x=(-27x)-63 |